Exploring the feasibility and effectiveness of a naturalistic family centered intervention to enhance early interactions in toddlers with Down syndrome - Ana Mendoza-García; Andrés Aparicio; Paulina Sofía Arango; Marcela Tenorio (Scientific Reports)
Abstract This study analyses the feasibility and effectiveness of BabyMICARE, a manualised intervention programme aimed at improving the interactions between caregivers and infants and toddlers with Down syndrome. The programme’s goal is to enhance caregivers’ sensitivity and reduce directivity during early interactions, particularly during play and daily routines. A pre-test and post-test design was used with 40 dyads of infants with Down syndrome and their caregivers, who were divided into a control group (n = 20) and an intervention group (n = 20), based on baseline scores in key interaction subscales. Sessions were conducted over 10 weeks by trained psychologists. Parent-infant interaction was assessed using the MACI coding system, which measures aspects such as sensitive responsiveness, directivity and the level of reciprocity between the parent and the child. The programme showed high feasibility, with a 100% attendance rate but some rescheduling. Caregivers evaluated it positively. The intervention group demonstrated significant improvements in five of eight MACI scales, particularly in sensitive responsiveness and nondirectiveness, while no changes were observed in the control group. The results suggest that BabyMICARE is a feasible and effective intervention for promoting more responsive, less directive interactions, which may be crucial in fostering children’s development.